The meaning of flow-based market coupling on redispatch measures in Austria - Lang, Lukas; Dallinger, Bettina; Lettner, Georg (Energy Policy, 2020)
Energy market modelling lacks an approach that tackles the implications of flow-based market coupling on congestion management in European electricity markets. Especially in the context of high shares of renewable energy, the topic of network congestion is becoming even more important. Usually, redispatch measures as a main part of congestion management are calculated on the basis of a simple load flow model incorporating net transfer capacities on the day-ahead market. In this paper, we suggest a modelling approach that incorporates the attributes of flow-based market coupling in the calculation of congestion management. An advanced load flow model is therefore already used to reflect the allocation process on the spot market. Retaining this result, necessary congestion management can be calculated on the basis of a more detailed network model representing the control areas’ exact transmission lines. Also, we conduct a comparison between the net transfer capacity- and the flow-based market coupling approach representing different levels of grid-granularities to show the importance of the grid model used for allocation on the European market for electricity. The results suggest, that necessary congestion management in the system is heavily dependent on the grid granularity, both in the sign and magnitude.<br
Keywords: Congestion management; Flow-based market coupling; Redispatch; Zonal pricing; Network topology